The use of collagen fleece for healing purposes - Jelušić, Damir; Siber, Stjepan (International Journal of Dental Biomaterials Research, 2022)
The collagen fleece is widely used biomaterial for healing in dental regeneration procedures. The aim of this work was to evaluate the regenerative potential of collagen sponge (collafleece®) in combination with other biomaterials being used in immediate implantation and sinus lift. For that reason, four patients were retrospectively analysed. The collagen fleece successfully supported the wound healing, controlled the bleeding, and assisted the healing of the Schneiderian membrane. The use of collafleece® led to successful treatment in combination with other biomaterials when used in immediate implantation and sinus lift.